Candolleomyces yunnanensis (Psathyrellaceae, Agaricales), a novel species from Yunnan Province, China - Zheng, De-Ge; Voto, Pietro; Tibpromma, Saowaluck; Lu, Wen-Hua; Han, Mei-Yan; Kumla, Jaturong; Suwannarach, Nakarin; Dai, Dong-Qin; Zhang, Li-Juan; Elgorban, Abdallah M.; Chukeatirote, Ekachai; Karunarathna, Samantha C. (Phytotaxa, 2025)
A new species, Candolleomyces yunnanensis, collected from Yunnan Province, China, is described based on morphological characteristics and molecular data. It is morphologically distinguished by its larger pileipellis cells, a pileus that is bronze brown (5E5) to yellowish brown (5E4) at the center and brownish grey (5E2) to birch grey (5C2) towards the margin, a fugacious veil, and the absence of pleurocystidia. Phylogenetic analyses of the nrITS, nrLSU, and tef-1α combined sequence confirm C. yunnanensis as a distinct member of Candolleomyces, forming a separate lineage from other Candolleomyces species.